2018
DOI: 10.3389/fmicb.2017.02633
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Lactoferrin and Lactoferrin-Derived Peptides Inhibit the Growth of Vibrio cholerae and Other Vibrio species

Abstract: Vibrio is a genus of Gram-negative bacteria, some of which can cause serious infectious diseases. Vibrio infections are associated with the consumption of contaminated food and classified in Vibrio cholera infections and non-cholera Vibrio infections. In the present study, we investigate whether bovine lactoferrin (bLF) and several synthetic peptides corresponding to bLF sequences, are able to inhibit the growth or have bactericidal effect against V. cholerae and other Vibrio species. The antibacterial activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 65 publications
(86 reference statements)
0
21
0
Order By: Relevance
“…They found that the suckled pups had substantially lower intestinal E. coli counts, interestingly with a corresponding increase in Lactobacillus numbers, and that the decrease in counts was reversed by feeding the pups hematin [ 39 ]. Iron-dependent anti-microbial effects of human and bovine Lf have been observed against a number of pathogens, including S. mutans, V. cholerae , and also P. aeruginosa , where iron chelation by Lf was found to stimulate a form of cell motility that inhibited biofilm formation by these bacteria [ 40 , 41 , 42 , 43 , 44 ].…”
Section: Direct Anti-microbial Effectsmentioning
confidence: 99%
“…They found that the suckled pups had substantially lower intestinal E. coli counts, interestingly with a corresponding increase in Lactobacillus numbers, and that the decrease in counts was reversed by feeding the pups hematin [ 39 ]. Iron-dependent anti-microbial effects of human and bovine Lf have been observed against a number of pathogens, including S. mutans, V. cholerae , and also P. aeruginosa , where iron chelation by Lf was found to stimulate a form of cell motility that inhibited biofilm formation by these bacteria [ 40 , 41 , 42 , 43 , 44 ].…”
Section: Direct Anti-microbial Effectsmentioning
confidence: 99%
“…In addition, some peptides may directly damage the bacterial membranes of different species/strains of Vibrio as it was shown for lactoferrin-derived peptides (Acosta-Smith et al, 2018). Whether these specific immune pathways are specifically upregulated by the diet used in this trial remains to be determined.…”
Section: Discussionmentioning
confidence: 83%
“…A specific bactericidal activity was reported for Lf and Lf chimera (synthetic Lf peptides). The Lf bacterial killing mechanism was attributed to membrane disruption followed by intracellular internalization [ 39 , 40 ]. Then, Lf or Lf chimera would result in alteration of gene expression.…”
Section: Pharmacological Activities Of Lactoferrinmentioning
confidence: 99%
“…The bactericidal activity of Lf-chimera, could be extended towards their ability to cause perturbation for bacterial cells, leading to programmed cell death type II. Moreover, membrane perturbation of V. Cholera was due to binding of Lf and Lf-peptides to specific sites on V. Cholera membrane [ 40 ].…”
Section: Pharmacological Activities Of Lactoferrinmentioning
confidence: 99%